Flexible, Structured Support for the Reuse of Online Learning Objects - Ramsay, Judith; McAteer, Erica; Harris, Rachel; Allan, Murray; Henderson, Jean (Proceedings of the International Conference on Networked Learning, 2004)
This paper outlines the development of a digitised tool for the repurposing of online resources for further and higher education. A digitised “learner guide template” that supports the semi-structured use of online educational resources was developed and then trialled by further education tutors. The findings of the trialling are presented here. The implications for the further development of the tool is discussed along with the insights gained into the pedagogical requirements of the learner guide template.